Association between β-blocker use and mortality in critically ill patients: a nested cohort study - Shmeylan A. Al Harbi; Khalid A. Al Sulaiman; Hani Tamim; Hasan M. Al-Dorzi; Musharaf Sadat; Yaseen Arabi (BMC, 2018)
Abstract Background β-blockers have several indications in critically ill patients and are commonly used. The aim of this study is to examine the relationship between the use of β-blockers in critically ill patients and mortality. Methods This was a nested cohort study in which all medical-surgical ICU patients (N = 523) enrolled in a randomized clinical trial of intensive insulin therapy (ISRCTN07413772) were grouped according to β-blocker use during ICU stay. To account for the indication of β-blockers, we constructed a propensity score using selected clinically-relevant and statistically-significant variables related to β-blocker exposure and outcome. The primary endpoints were all-cause ICU and hospital mortality. Secondary endpoints were the development of severe sepsis during ICU stay, ICU and hospital length of stay, and mechanical ventilation duration. Using multivariable models, we adjusted the associations of β-blockers and these outcomes to the propensity score. Results Of the 523 patients enrolled in the study, 89 (17.0%) received β-blockers during their ICU stay. There were no significant associations between β-blocker therapy and ICU mortality (adjusted odds ratio [aOR] 1.56, 95% confidence interval [CI] 0.83-2.9, P = 0.16), hospital mortality (aOR 1.09, 95% CI 0.99-1.20, P = 0.73), the risk of ICU-acquired severe sepsis (aOR 1.67, 95% CI 0.95-2.97, P = 0.08), mechanical ventilation duration (P = 0.17), or ICU length of stay (P = 0.22). However, β-blocker use was associated with increased ICU and hospital mortality among nondiabetic patients (aOR 2.93, 95% CI 1.19-7.23, and 2.43, 95% CI 1.05-5.64, respectively). Conclusions Our study showed that β-blockers during the ICU stay had no significant association with mortality or morbidity. However, β-blocker therapy was associated with increased mortality in non-diabetic patients. Trial registration ISRCTN07413772; (dated 13.07.2005).